Altering experienced utility the impact of story writing and self referencing on preferences - West, Patricia M.; Huber, Joel; Kyeong, Sam Min (2004)
This article examines the impact of writing stories on the evaluation of consumption objects. Generating a story creates greater liking for a painting than generating a dialogue about it. The positive impact of stories does not derive from generating more positive thoughts. Instead, stories generate fewer affective thoughts than do dialogues. The importance of generated stories derives from deeper elaboration, providing enhanced recollection of the coherent narrative, ease of generation, and more favorable attitudes toward the task. This work extends prior research on narratives and self referencing by making the consumer an active participant in the generation process, setting a rich agenda for future research.
Includes bibliographical references.
Downloaded from http://www.jstor.org/stable/3692819
Keywords: Story writing